2020
DOI: 10.1021/acs.jpcc.0c05943
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Optical Magnetism in Gold and Silver Probed by Dynamic Metamolecules

Abstract: Here, we report plasmonic metamolecules with dynamically controllable optical magnetism. A dynamic metamolecule (DMM) is constructed by decorating gold or silver nanobeads on a thermoresponsive poly(N-isopropylacrylamide) (PNIPAM) hydrogel sphere, which generates uniform coresatellite-type assembly structures with an interbead distance, allowing for strong interparticle coupling. Experimental and simulation results revealed strong magnetic dipole and quadrupole modes observable in the far field both for gold a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(50 citation statements)
references
References 47 publications
2
42
0
Order By: Relevance
“…Hydrogels are water-absorbing polymers well-known for their bio-compatibility and stimuli-responsivity. The reversible volume phase transition and elastic behaviors of hydrogel have enabled the design of smart materials such as temperature-responsive drug delivery and wound healing materials [ 3 , 4 , 5 ], remotely controlled soft actuators [ 6 , 7 ], stimuli-responsive plasmonic materials [ 8 ], flexible sensors [ 9 , 10 ], etc. In addition, a sparse polymer network in an aqueous medium can be used as a matrix to incorporate nanoparticles [ 11 ] and microreactors [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are water-absorbing polymers well-known for their bio-compatibility and stimuli-responsivity. The reversible volume phase transition and elastic behaviors of hydrogel have enabled the design of smart materials such as temperature-responsive drug delivery and wound healing materials [ 3 , 4 , 5 ], remotely controlled soft actuators [ 6 , 7 ], stimuli-responsive plasmonic materials [ 8 ], flexible sensors [ 9 , 10 ], etc. In addition, a sparse polymer network in an aqueous medium can be used as a matrix to incorporate nanoparticles [ 11 ] and microreactors [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These metamolecules have seen great interest in recent years due to their ease of synthesis, tunability, and potent magnetic resonances. [11][12][13] We have recently demonstrated that the magnetic resonance of these metamolecules can be dynamically controlled using hydrogel cores that can change their core size upon heating (which we call dynamic metamolecules or DMMs). 12 DMMs have been shown to produce experimentally realizable magnetic dipoles and even quadrupoles in solution phase, even in ensemble measurements in both gold and silver, and their properties can be controlled by adjusting the temperature of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] We have recently demonstrated that the magnetic resonance of these metamolecules can be dynamically controlled using hydrogel cores that can change their core size upon heating (which we call dynamic metamolecules or DMMs). 12 DMMs have been shown to produce experimentally realizable magnetic dipoles and even quadrupoles in solution phase, even in ensemble measurements in both gold and silver, and their properties can be controlled by adjusting the temperature of the solution. 12 This is significant, as tunable higher order magnetic modes display unique scattering behaviors 14 that could serve to further expand the range of applications these systems can provide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, significant efforts have been made in this area, which led to tremendous advances in our ability to control the structure and properties of plasmonic nanoparticles. [13] In often cases, plasmonic nanoparticles are combined with other molecular or nanoscale materials such as molecular crosslinkers, [14] block copolymers, [15] stimuli-responsive materials, [16] biological molecules, [17] and other functional inorganic nanoparticles. [18] While earlier studies focused on generating a series of static assemblies with tunable, yet permanent, structural parameters and properties, current research involves the development of dynamic nanostructures programmed to undergo on-demand structural transformations that can alter their properties or can trigger motion.…”
mentioning
confidence: 99%